The New Nature Writing Rethinking the Literature of Place - Smith, Jos (Environmental Cultures, 2017)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. In the last decade there has been a proliferation of landscape writing in Britain and Ireland, often referred to as 'The New Nature Writing'. Rooted in the work of an older generation of environment-focused authors and activists, this new form is both stylistically innovative and mindful of ecology and conservation practice. The New Nature Writing: Rethinking the Literature of Place connects these two generations to show that the contemporary energy around the cultures of landscape and place is the outcome of a long-standing relationship between environmentalism and the arts. Drawing on original interviews with authors, archival research, and scholarly work in the fields of literary geographies, ecocriticism and archipelagic criticism, the book covers the work of such writers as Robert Macfarlane, Richard Mabey, Tim Robinson and Alice Oswald. Examining the ways in which these authors have engaged with a wide range of different environments, from the edgelands to island spaces, Jos Smith reveals how they recreate a resourceful and dynamic sense of localism in rebellion against the homogenising growth of "clone town Britain."